Electrophoretic deposition of chitosan coatings on the Ti15Mo biomedical alloy from a citric acid solution. Issue 23 (1st April 2020) - Szklarska, Magdalena; Łosiewicz, Bożena; Dercz, Grzegorz; Maszybrocka, Joanna; Rams-Baron, Marzena; Stach, Sebastian
Abstract : Chitosan biocoatings were successfully deposited on the Ti15Mo alloy surface via cataphoretic deposition from a solution of 1 g dm −3 of chitosan in 4% (aq) citric acid. Abstract : Chitosan biocoatings were successfully deposited on the Ti15Mo alloy surface via cataphoretic deposition from a solution of 1 g dm −3 of chitosan in 4% (aq) citric acid. The influence of the cataphoretic deposition parameters on quality and morphology of the obtained coatings were investigated using fluorescence and scanning electron microscopy. The functional groups' presence in chitosan chine were confirmed by ATR-FTIR methods. X-ray analysis revealed the amorphous structure of the chitosan coatings on the Ti15Mo alloy surface. The conducted studies also include assessing the abrasion resistance and adhesion to the substrate of the obtained chitosan coatings. The results show that utilizing the citric acid as a solvent results in the formation of pore free coatings. The yield of the electrophoretic deposition process was in the range of 2–10 mg of deposited chitosan per 1 cm 2 . The obtained coatings through the unique properties of chitosan are a promising biomaterial for application in medicine.